Mental health treatment for children and adolescents - Corcoran, Jacqueline (New York ; Oxford : Oxford University Press, 2010)
Mental health problems disrupt the lives of many young people and their families, putting them at risk for instability as adults. This is particularly true for children from vulnerable populations, such as those in the child welfare or juvenile justice systems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child psychiatry; Adolescent psychiatry; Evidence-based psychiatry